Development of Flexible Polyacrylonitrile‐Based Carbon Nanofibrous Yarns Through Optimization of Heat Treatment Processes - Marzieh Ataei; Maryam Yousefzadeh; Majid Montazer; Seeram Ramakrishna (Macromolecular Materials and Engineering, 2025)
Abstract This study presents an optimized dual‐nozzle electrospinning method for fabricating high‐performance carbon nanofibrous yarns (CNY). By implementing controlled uniaxial tension during oxidative stabilization, nanofiber alignment, molecular orientation, and mechanical performance are significantly improved. The effect of the uniaxial tension and heat treatment on the CNY's physical and mechanical properties was investigated using SEM, DSC, FTIR, Raman, and tensile mechanical testing. The findings demonstrate a significant improvement in tensile strength and modulus, increasing from 5.38 ± 1.41 to 40.48 ± 4.74 MPa and from 27 ± 6.11 to 297.15 ± 68.29 MPa, respectively. This represents a 659% improvement in tensile strength and a nearly 1000% increase in modulus, highlighting the efficacy of the method. Compared to previous studies, this work introduces a low‐temperature, scalable, and energy‐efficient process that significantly enhances the mechanical properties, positioning it as an ideal candidate for applications in wearable electronics, energy storage, and advanced composite materials. The findings establish a new benchmark in carbon nanofiber technology, offering a cost‐effective and highly reproducible process for the mass production of high‐strength CNYs.